Metal Halide Regulated Photophysical Tuning of Zero‐Dimensional Organic Metal Halide Hybrids: From Efficient Phosphorescence to Ultralong Afterglow. (7th October 2020) - Xu, Liang‐Jin; Plaviak, Anna; Lin, Xinsong; Worku, Michael; He, Qingquan; Chaaban, Maya; Kim, Bumjoon J.; Ma, Biwu
Abstract: The photophysical tuning is reported for a series of tetraphenylphosphonium (TPP) metal halide hybrids containing distinct metal halides, TPP2 MX n (MX n =SbCl5, MnCl4, ZnCl4, ZnCl2 Br2, ZnBr4 ), from efficient phosphorescence to ultralong afterglow. The afterglow properties of TPP + cations could be suspended for the hybrids containing low band gap emissive metal halide species, such as SbCl5 2− and MnCl4 2−, but significantly enhanced for the hybrids containing wide band gap non‐emissive ZnCl4 2− . Structural and photophysical studies reveal that the enhanced afterglow is attributed to stronger π–π stacking and intermolecular electronic coupling between TPP + cations in TPP2 ZnCl4 than in the pristine organic ionic compound TPPCl. Moreover, the afterglow in TPP2 ZnX4 can be tuned by controlling the halide composition, with the change from Cl to Br resulting in a shorter afterglow due to the heavy atom effect. Abstract : Zero‐dimensional Ph4 P + (TPP + ) metal halide hybrids have been developed to exhibit distinct photophysical properties, from highly efficient phosphorescence to ultralong afterglow. The afterglow properties of Ph4 P + cations could be suspended for the hybrids containing low band gap emissive metal halide species, such as SbCl5 2− and MnCl4 2−, but enhanced for the hybrid containing wide band gap non‐emissive ZnCl4 2− .